1992
DOI: 10.1002/1098-108x(199201)11:1<63::aid-eat2260110109>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder symptoms among adolescents in the United States and Spain: A comparative study

Abstract: The severity of eating disorder symptoms and interest in weight reduction vary among cultures and nationalities. The present study is the first to directly compare the extent of these problems between two Western nations. Although several reports have emerged from other European countries, this is the first study of eating disorder symptoms among Spanish youth. There were more American girls with bulimia nervosa symptoms; the overall level of eating disorder symptoms was higher among the Americans; and more Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 24 publications
3
17
0
2
Order By: Relevance
“…This may make those who are already in the lower end of the normal-weight range to become underweight. The finding for the normal-weight males in this study conforms to those of other authors who found that overestimation of BI is a common finding in the general population 22,23,24 . Indeed, a large percentage of men idealise a heavily muscular, yet lean physique 26,27 .…”
Section: Resultssupporting
confidence: 92%
“…This may make those who are already in the lower end of the normal-weight range to become underweight. The finding for the normal-weight males in this study conforms to those of other authors who found that overestimation of BI is a common finding in the general population 22,23,24 . Indeed, a large percentage of men idealise a heavily muscular, yet lean physique 26,27 .…”
Section: Resultssupporting
confidence: 92%
“…18 Our results regarding BMI and body self-evaluation are in accordance with international standards (72.9% of the women in our study would like to weigh less). According to the literature, 70% of American women and 48% of Spanish women would like to be thinner, 19 and 50% of Australian women would like to weigh 7 kg less. 20 National studies on the topic have shown that 28.1% of Brazilian medical students feel fat even when they are normal weight 10 ; in addition, two thirds of the population assessed in Pelotas (RS) either would like to weigh less or feel fat, when in fact only one third of 18 -Rev Psiquiatr Rio Gd Sul.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in eating disturbances and BID between the United States and Europe have been sporadically documented (Mangweth, Pope, & Hudson, 1994;Raich et al, 1992), the United States consistently showing higher rates. These differences were initially attributed to variable diagnostic practices rather than to cultural differences between the United States and Europe (Nasser, 1997).…”
Section: Discussionmentioning
confidence: 99%